Fractionation of toxic metal Pb from truly dissolved and colloidal phases of seaward rivers in a coastal delta - Ren, Peng; Schmidt, Bjorn V.; Liu, Qun; Wang, Shuzhen; Liu, Xinyan; Liu, Kai; Shi, Dalei (Frontiers in Marine Science, 2023)
Colloidal phase is an important intermediate carrier of Pb in the natural river water. It is important to monitor the transport-transformation behavior of Pb in colloidal phase in seaward water because this behavior related the input pollution and environment risk of the sea, especially in the coastal delta area. In this study, the fraction behavior and distribution of toxic Pb from truly dissolved phase to different colloidal phases in seven seaward rivers in the Yellow River Delta was investigated. The concentration of total dissolved Pb, truly dissolved Pb, and colloidal Pb was 0.99-40.09 μg L-1, 0.40-8.10 μg L-1, and 0.60-35.88 μg L-1. In freshwater of all the river, the main component of total dissolved Pb (about >50%) was truly dissolved Pb but was the colloidal Pb (>80%) in seawater environment. The dramatic enhancement of salinity induced a deposition (about ~94%) of all forms of Pb from estuary water to sediment in winter. However, this sedimentation behavior of colloidal Pb gradually decreases (Shenxiangou River) when the river salinity approaches seawater salinity (~S=29). In the port industrial (Xiaoqinghe River) and mariculture (Yongfenghe River) estuarine areas with extensive use of seawater, the deposition behavior of colloidal Pb (<15%) is less affected by the change of salinity. This suggests that human activity can lead to the spread of Pb to the offshore environment. The concentration of 100 kDa-0.22 μm Pb have a close liner relationship with the total colloidal Pb. And its variation is minimally affected by salinity compared to other colloidal components. Also, the correlation between the molecular weight and aromaticity of CDOM and the colloidal Pb suggests that macromolecules in seawater will be important transport carriers of Pb. In all, the truly dissolved Pb is the main transport form of dissolved Pb in freshwater river; however, in brackish water at estuaries, the colloidal matter gradually becomes the main transport carrier. Surging salinity immobilize truly dissolved Pb in the estuarine region, but colloidal matter inhibits this deposition. Colloidal matter is an important conversion between land-sea transport of Pb by transformation between different fraction in seaward rivers.